Effect Of Neurodynamic Mobilization On Reducing Sensori neural Symptopms In Dawung Village Wood Craftsmen With The Risk Of Hand Arm Vibartion Syndrome (HAVS) - Dina Azizah Wulandari; Siti Ainun Ma'rufa; Sri Sunaringsih Ika Wardojo (Fakultas Keperawatan dan Fisioterapi Institut Kesehatan Medistra Lubuk Pakam, 2023)
Hand Arm Vibration Syndrome (HAVS) is a disease caused by working with tools that produce vibrations that are transmitted to the arms and hands. Prolonged use of vibrating devices can cause sensorineural disturbances with complaints of numbness, tingling and decreased sensitivity. This is due to damage to the mechanoreceptors of myelinated A-? afferent nerve fibers due to exposure to vibration when working with vibrating tools. Neurodynamic mobilization functions to restore the plasticity of the nervous system and the ability of the nervous system. This study aims to determine the effect of neurodynamic mobilization on reducing sensorineural symptoms with the risk of HAVS in wood craftsmen in Dawung Village. The design of this study used a pre-experimental one group pretest-posttest design method. There are 15 samples of wood craftsmen who meet the criteria. The research instrument used the Stockholm workshop scale with data analysis using the Wilcoxon test. The results of the statistical test showed that the final result was p = 0.000, (p <0.05) which means that the effect of neurodynamic mobilization on reducing sensorineural symptoms in wood craftsmen in Dawung Village is at risk of HAVS. These results indicate that the neurodynamic mobilization intervention has effectiveness in increasing blood circulation in the nerves. The conclusion obtained is that neurodynamic mobilization has an effect on reducing sensorineural symptoms in wood craftsmen in Dawung Village with the risk of HAVS.